Dyslipidemia and adherence to the Mediterranean diet in Croatian HIV-Infected patients during the first year of highly active antiretroviral therapy - Turčinov, Drago (Array, 2009)
Abstract: We investigated the association of adherence to the Mediterranean diet and other risk factors for dyslipidemia in HIV-infected Croatian patients during the first year of highly active antiretroviral therapy (HAART). Adherence to the Mediterranean diet was determined by a 150-item questionnaire; a 0 to 9-point diet scale was created that stratified respondents as having low adherence (<4 points) and moderate to high adherence (ł 4 points). We interviewed 117 participants between May 2004 and June 2005 and abstracted their serum lipid measurements taken during the first year of HAART. The values of total cholesterol, HDL-cholesterol, LDL-cholesterol and triglycerides increased most prominently in the first 3 to 6 months after initiation of HAART (average increase at 3 months: 25% for total cholesterol, 22% for LDL-cholesterol, 18% for HDL-cholesterol and 43% for triglycerides). A Mediterranean diet and physical activity had no effect on serum lipids. The mean total cholesterol was higher in participants receiving a combination of a non-nucleoside reverse transcriptase inhibitor and a protease inhibitor compared to participants receiving a combination of nucleoside analogs with a non-nucleoside analog or a combination of nucleoside analogs and a protease inhibitor. Among individual drug treatments, indinavir/ritonavir had the most unfavorable lipid profile. We conclude that adherence to a Mediterranean diet does not influence serum lipid profiles during the first year of HAART